Exploring the Design Guidelines of Large Screen UI for Optimal Viewing Experience on Smart TV - Kim, Donghyun; Im, Youngjae (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
With the prevalence of large-screen smart TVs, viewing experiences are becoming more interactive. This technological advance makes an increase in information density and diverse layouts. This study aims to derive ergonomic design guidelines for TV UI to optimize the viewing experience. Fifteen subjects participated in the main test, performing tasks consisting of visual navigation and remote manipulation according to twelve different alternatives. The experimental variables were selected as screen size, information quantity and layout. The dependent measures were collected on performance time, visual cognitive satisfaction and manipulation satisfaction. The results revealed that screen size, information quantity, and layout had significant effects on visual satisfaction. Larger screens with more information enhanced visual cognitive satisfaction. Screen size and information quantity influenced on manipulation satisfaction. Meanwhile, information quantity and layout had greater impacts on user performance. This research provides appropriate design guidelines for smart TV UI and practical implications for product developers.